'Share your views'-international consultation informs a patient engagement strategy for the Multinational Association of Supportive Care in Cancer - Wardill, Hannah R; Cheung, Yin Ting; Boltong, Anna; Charalambous, Andreas; Koczwara, Bogda; Lustberg, Maryam; Tomlins, Elaine; Britto, Joanne M (My University, 2022)
Engaging with patients and the public (consumers and community) enhances the relevance of cancer control developments; however, challenges remain to integrate into processes. Medical and other professional societies are well-positioned to foster and endorse best practice.
Keywords: Patient and public advocacy; Consumer and community involvement; People afected by cancer; Supportive cancer care; Terminology